Dietary and lifestyle factors effect erythrocyte PIG-A mutant frequency in humans. (12th October 2020) - Lawrence, Rachel; Haboubi, Hasan; Williams, Lisa; Doak, Shareen; Jenkins, Gareth
Abstract: It is well understood that poor diet and lifestyle choices can increase the risk of cancer. It is also well documented that cancer is a disease of DNA mutations, with mutations in key genes driving carcinogenesis. Measuring these mutations in a minimally invasive way may be informative as to which exposures are harmful and thus allow us to introduce primary preventative measures, in a bid to reduce cancer incidences. Here, we have measured mutations in the phosphatidylinositol glycan class A ( PIG-A ) gene in erythrocytes from healthy volunteers ( n = 156) and from non-cancer patients attending the local endoscopy department ( n = 144). The X-linked PIG-A gene encodes an enzyme involved in glycosylphosphatidylinositol (GPI) anchor synthesis. A silencing mutation in which leads to the absence of GPI anchors on the extracellular surface which can be rapidly assessed using flow cytometry. The background level of PIG-A mutant erythrocytes was 2.95 (95% CI: 2.59–3.67) mutant cells (10 −6 ). Older age increased mutant cell frequency ( P < 0.001). There was no difference in mutant cell levels between males and females ( P = 0.463) or smokers and non-smokers ( P = 0.186). In the endoscopy group, aspirin users had lower mutant frequencies ( P = 0.001). Further information on diet and exercise was available for the endoscopy patient group alone, where those with a higher health promotion index score had lower mutant frequencies ( P = 0.011). Higher dietary intake of vegetables reduced mutant cell levels ( P = 0.022). Participants who exercised for at least 1 h a week appeared to have reduced mutant frequencies than those who did not exercise, although this was not statistically significant ( P = 0.099). This low background level of mutant erythrocytes in a population makes this assay an attractive tool to monitor exposures such as those associated with lifestyles and diet, as demonstrated here.